Study of Second and Fourth Digit Lengths and Their Ratios With Physical Attributes in Nepali Population - Satyal, Biswas; Satyal, Abhishek (Journal of Nepalgunj Medical College, 2018)
Introduction: The ratio of the lengths of the index and the ring finger (2D:4D ratio) is generally different between men and women. A number of studies have shown a correlation between the 2D:4D digit ratio and various physical and behavioral traits. The aim of the present study is to investigate the association of the index (2nd) and ring (4th) digit ratios with some physical traits in Nepal population.Material & Method: 200 students (100 males and 100 females) between ages of 18 years and above were randomly selected with exclusion of those with hand deformities. The digit lengths were measured from the basal crease to the tips usingvernier calipers. The 2D:4D ratios were determined for each subject while height and weight were used to calculate the body mass index and data analyzed. The study was conducted between January 2018 to November 2018.Result: The result of the anthropometric study of the differences in index (2D) and ring (4D) and their ratios shows that there was a significant difference between the length of index finger (2D), ring finger (4D) and the ratios of right hand's 2D:4D in both males and females. There was appositive correlation between the second digit length and Height and weight in males and females both on right and left sides. The 2D:4D ratio for both left and right hand did not show any positive correlation with height, weight or BMI of an individual.